Biomarkers in the development of individualized treatment regimens for colorectal cancer - Crutcher, Madison; Waldman, Scott (Frontiers in Medicine, 2022)
Introduction Colorectal cancer (CRC) is the third most common and second most deadly malignancy in the world with an estimated 1. 9 million cases and 0.9 million deaths in 2020. The 5-year overall survival for stage I disease is 92% compared to a dismal 11% in stage IV disease. At initial presentation, up to 35% of patients have metastatic colorectal cancer (mCRC), and 20–50% of stage II and III patients eventually progress to mCRC. These statistics imply both that there is a proportion of early stage patients who are not receiving adequate treatment and that we are not adequately treating mCRC patients. Body Targeted therapies directed at CRC biomarkers are now commonly used in select mCRC patients. In addition to acting as direct targets, these biomarkers also could help stratify which patients receive adjuvant therapies and what types. This review discusses the role of RAS, microsatellite instability, HER2, consensus molecular subtypes and ctDNA/CTC in targeted therapy and adjuvant chemotherapy. Discussion Given the relatively high recurrence rate in early stage CRC patients as well as the continued poor survival in mCRC patients, additional work needs to be done beyond surgical management to limit recurrence and improve survival. Biomarkers offer both a potential target and a predictive method of stratifying patients to determine those who could benefit from adjuvant treatment.